The Analytical Solution of Some Fractional Ordinary Differential Equations by the Sumudu Transform Method - Bulut, Hasan; Baskonus, Haci Mehmet; Belgacem, Fethi Bin Muhammad (Hindawi Ltd, 2013)
We introduce the rudiments of fractional calculus and the consequent applications of the Sumudu transform on fractional derivatives. Once this connection is firmly established in the general setting, we turn to the application of the Sumudu transform method (STM) to some interesting nonhomogeneous fractional ordinary differential equations (FODEs). Finally, we use the solutions to form two-dimensional (2D) graphs, by using the symbolic algebra package Mathematica Program 7.
Keywords: Variational Iteration Method; Decomposition Method